PKM PELATIHAN ECOPRINT BAGI DHARMA WANITA PERSATUAN DINAS KEHUTANAN PROVINSI PAPUA BARAT - Santi, Darma; Mangallo, Bertha; Somar, Evelina; Novitasari, Agnes Dyah; Susilowati, Susilowati; Santoso, Bimo Budi; Sirampun, Alfhons Daniel; Sumarna, Sabir; Morin, Jacson Viktor; Langsa, Markus Heryanto; Taher, Achmad; Islam, Muhammad Fajar (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2025)
This training was designed to introduce ecoprint techniques to members of the Women's Dharma Association of the West Papua Provincial Forestry Service, emphasizing its potential as a community-based business opportunity. The activity utilized natural materials readily available in the surrounding environment, such as butterfly pea leaves and flowers, teak leaves, and other local foliage. The training was conducted in stages, beginning with an introduction to the basic concepts of eco-printing, followed by hands-on practice using two main techniques: pounding and steaming. These techniques were applied to cloth tote bags and ceramic mugs. The results showed that participants demonstrated a higher level of proficiency in producing eco prints using the steaming technique compared to the pounding method.